Chemotaxis: signalling modules join hands at front and tail - Postma, Marten (2004)
Chemotaxis is the result of a refined interplay among various intracellular molecules that process spatial and temporal information. Here we present a modular scheme of the complex interactions between the front and the back of cells that allows them to navigate. First, at the front of the cell, activated Rho-type GTPases induce actin polymerization and pseudopod formation. Second, phosphatidylinositol-3,4,5-trisphosphate (PtdIns(3,4,5)P(3)) is produced in a patch at the leading edge, where it binds pleckstrin-homology-domain-containing proteins, which enhance actin polymerization and translocation of the pseudopod. Third, in Dictyostelium amoebae, a cyclic-GMP-signalling cascade has been identified that regulates myosin filament formation in the posterior of the cell, thereby inhibiting the formation of lateral pseudopodia that could misdirect the cell.